The Influence of Environmental, Social, and Governance (ESG) on Financial Distress: Empirical Study of Banking Sector Companies Listed on the IDX for the Period 2021–2024 - Riranne Alfatihannas Syabila; Desmy Riani; Hurriyaturrohman (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2026)
Financial distress is a condition of financial difficulty experienced by a company before bankruptcy, which can be influenced by the implementation of Environmental, Social, and Governance (ESG). ESG serves as an important indicator in assessing a company's sustainability and responsibility toward the environment, society, and governance. This study aims to determine the influence of environmental, social, and governance on financial distress in banking sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. Financial distress in this study is measured using the Z-Score, where a higher Z-Score indicates more stable financial conditions and a lower risk of financial distress. Secondary data were obtained from company annual reports and ESG data sourced from Bloomberg. The population encompasses all banking sector companies listed on the IDX. Using purposive sampling, 19 companies were selected with a total of 76 observations. Panel data regression analysis was conducted using EViews 13 software. The results show that environmental does not significantly affect financial distress, meaning that environmental performance has not yet become a determining factor in explaining the financial stability of banking companies during the study period. Social also does not significantly affect financial distress, indicating that social responsibility practices have not directly influenced banks’ financial distress conditions. Governance has a significant effect on financial distress, meaning that stronger corporate governance contributes to better financial stability and reduces the possibility of financial distress. Meanwhile, ESG Score does not significantly affect financial distress, indicating that the overall ESG performance has not been strong enough to explain variations in financial distress among banking companies.